P059 Diet controls segmented filamentous bacteria in driving Crohn's disease-like inflammation in TNFdeltaARE mice. (21st January 2022) - Metwaly, A; Calasan, J; Waldschmitt, N; Khaloian, S; Häcker, D; Ahmed, M; Butto, L F; Hammoudi, N; Le Bourhis, L; Mayorgas, A; Siebert, K; Basic, M; et al.
Abstract: Background: Crohn's disease (CD)-like inflammation in TNFdeltaARE mice (ARE) mice is triggered by dysbiotic gut microbial communities. Similar to the therapeutic effect of exclusive enteral nutrition in CD, dietary intervention using semi-synthetic experimental diet prevents disease development in ARE mice. The aim of this study is to identify the causal microbial cues responsible for CD-like inflammation and to dissect the protective role of diet in ARE mice. Methods: Bacterial communities in ARE and wildtype (WT) mice were profiled by 16S rRNA gene sequencing, FISH and qPCR. Germfree WT and ARE mice were colonized with segmented filamentous bacteria (SFB) from dysbiotic ARE mice. Disease activity, cytokine expression, mucosal immune cell infiltrates as well as Paneth and goblet cells phenotypes were assessed in murine ileal and colonic tissue. To assess the influence of diet on disease development, ARE mice were fed either chow, purified semi-synthetic experimental diet (SED) or fiber-rich diet. Impact of SFB on ileo-colonic inflammation was tested in additional mouse models (XIAP-/- and IL10 -/-). Mucosal biopsies from adult and pediatric IBD patients (N=407) were screened for the presence of human SFB using SFB-specific PCR primers. Results: Under specific pathogen-free (SPF) conditions, ARE mice developed CD-like ileal inflammation which correlated strongly with increasing abundance of SFB. Mono-colonization of germfree ARE mice with SFB resulted in severe enterocolitis. Parallel to high tissue levels of TNF and IL-17, SPF-mediated inflammation was associated with neutrophil infiltration and the expansion of IFNγ expressing Th1 cells in the mucosa. Loss of Paneth and goblet cell function allowed SFB to penetrate mucus layers towards the epithelium. SED eradicated SFB and completely abolished inflammation in ARE mice. In contrast, fiber-rich diet partially restored SFB colonization and led to increased levels of inflammatory cytokines. SFB mono-colonization of GF XIAP -/- and IL10 -/- failed to induce inflammation, emphasizing host specificity to the mucosa-adherent SFB. Presence of SFB was confirmed in 12 ileal and 11 colonic mucosal biopsies from IBD patients with active or inactive disease. Conclusion: We identified a novel pathogenic role of SFB in driving severe CD-like ileo-colonic inflammation characterized by loss of Paneth and goblet cell functions in ARE mice. Detection of SFB in mucosal biopsies of patients with IBD opens new perspectives about therapeutic strategies targeting SFB-mediated processes. Purified diet antagonized SFB colonization and prevented disease development in ARE mice in contrast to fiber-rich diet, clearly demonstrating the important role of diet in modulating a novel IBD-relevant pathobiont.